Multilingual and multicultural backgrounds: an exploration of language attitudes toward restrictive language policies at the college level - McCord, Ann Elizabeth (My University, 2025)
Restrictive language policies are formed by language ideologies that prevail among communities, along with the individual attitudes that support the furthering of language ideologies, whether supportive of or adverse to multilingual interests. Currently, the literature demonstrates that both second language learners (L2s) and heritage language learners of Spanish (HLLs) may perceive the restriction of language policies negatively, although some results have been mixed, yielding both positive and negative student responses (Shvidko, 2017; Vidana, 2020; Valdés, 2023). The types of language policies reviewed in current studies are limited to rules at the local, institutional level– typically taking place in a university setting. For language instructors, previous research shows they may consider the challenges standard language ideologies pose for the linguistic practices of HLLs– within the bounds of Spanish second language courses or language courses designed specifically for the needs of HLLs (Showstack, 2024). In a policymaking role as an instructor, Showstack (2024) determined that instructors' personal and linguistic backgrounds play a large role in their classroom policies and legitimation of HLLs’ linguistic practices. Until now, the attitudes of several student profiles (L2s and HLLs) and their instructors (language faculty) towards language policies at the state and federal levels have yet to be explored in a cross-sectional study. Furthermore, to what extent teachers’, L2s’, and HLLs’ personal and linguistic histories play a role in their understanding of language ideologies and attitudes towards the policies that embody them remains unknown. This study builds upon the small corpus of studies related to restrictive language policies, language ideologies, and language attitudes to examine the extent to which participants' upbringings, educational experiences, and professional preparation could affect their views towards restrictive language policies.
Keywords: Language attitudes; Language ideologies; Restrictive language policies; Midwest; Language education